2003
DOI: 10.1302/0301-620x.85b7.13882
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre-operative bone mineral content of the proximal tibia on revision rate after uncemented knee arthroplasty

Abstract: Between 1986 and 1991, 106 patients (127 knees) underwent uncemented knee arthroplasty for osteoarthritis. There were 106 total knee arthroplasties and 21 medial unicompartmental knee arthroplasties. The arthroplasties were evaluated for aseptic loosening during the year 2000. For total arthroplasty we used 77 porous-coated anatomic prostheses and 29 press-fit condylar prostheses. The mean bone mineral content of the proximal tibia, measured the day before surgery using dual-photon absorptiometry was 5.48 g/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…This has been suggested as a factor contributing to implant migration and loosening in TKA [18,31] and UKA [14,29,30]. Although studies have reported BMD loss ranging from 5% to as much as 36.4% none has been able to correlate this to failure of the implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been suggested as a factor contributing to implant migration and loosening in TKA [18,31] and UKA [14,29,30]. Although studies have reported BMD loss ranging from 5% to as much as 36.4% none has been able to correlate this to failure of the implants.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies with limited numbers did not correlate BMD loss with clinical failure, some authors believe diminished BMD is a factor in implant migration and loosening [18,31]. The same failure mechanism has been proposed for UKA [14,29,30].…”
Section: Introductionmentioning
confidence: 94%
“…Quality of proximal tibial bone mineral density (BMD) is a factor that may determine migration of implants after TKA [6,8,13,25]. Dual-energy xray absorptiometry (DEXA) studies suggest proximal tibial BMD declines after TKA [1,5,9,12,17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The quantity and quality of cancellous bone vary widely among individuals. Many patients are not considered candidates for cementless total knee arthroplasty because of concerns about insufficient cancellous bone in the proximal part of the tibia [13][14][15][16] . Biological enhancement of cancellous bone quantity and osseointegration would provide one mechanism to improve the outcomes of cementless total knee arthroplasty.…”
mentioning
confidence: 99%